Analyzing longitudinal qualitative data: the application of trajectory and recurrent cross-sectional approaches. (December 2016) - Grossoehme, Daniel; Lipstein, Ellen
Abstract Background Longitudinal qualitative research methods can add depth and understanding to health care research, especially on topics such as chronic conditions, adherence and changing health policies. In this manuscript we describe when and how to undertake two different applied approaches to analyzing longitudinal qualitative data: a recurrent cross-sectional approach and a trajectory approach. Results A recurrent cross-sectional approach is most appropriate when the primary interest is comparing two time points, such as before and after a policy change, or when a cohort cannot be maintained, such as a study in which some participants are expected to die. In contrast, a trajectory approach is most appropriate when the purpose of the research is to understand individuals' experiences over time or to understand longitudinal healthcare processes. Conclusions Longitudinal qualitative research has the potential to be a powerful approach to understanding the complexities of health care: from relationships between providers and patients, to the experience of chronic disease, to the impact of health policy. Such research will be strengthened by careful consideration of the research question at hand, followed by application of the appropriate analytic approach.